Etika Bisnis Islam Pada Pedagang Kuliner Di Pusat Pasar Kota Medan - Sibuea, Nurhalimah; Subaktiar, Subaktiar; Adriansyah, Adriansyah; Hakim, Mukti (Journal of Computer Science and Information System(JCoInS), 2026)
This study used a qualitative approach with field research. The subjects were food and beverage vendors at the Medan City Market Center. Data sources consisted of primary and secondary data, with data collection techniques using interviews, observation, and documentation. The results of the study indicate that 1). Food vendors at the market center are able to implement three aspects of Islamic business axioms: equilibrium, free will, and responsibility, but have not been able to implement the aspect of unity. 2). Obstacles faced by food vendors in implementing Islamic business ethics include the idea that trading is more important than fulfilling obligations as Muslims. Furthermore, there are obstacles in inadequate waste management regulations, so good cooperation is expected between food vendors, buyers, and the relevant government. 3). The implementation of Islamic business ethics among food vendors at the market center aims to increase education about the importance of trading based on Islamic business ethics, thus enabling food vendors to conduct transactions properly and in accordance with Islamic law.